Analisis Implementasi Kurikulum Merdeka pada Satuan Pendidikan Anak Usia Dini - Wahyuni, Sri; Sumarno, Sumarno; Dwijayanti, Ida (Medan Resource Center, 2024)
This research addresses the importance of implementing an independent curriculum, especially considering its mandatory adoption in all educational units by 2024. The study aims to elucidate the concept of an independent curriculum at Pertiwi Gondangan Kindergarten. Utilizing a literature study approach with observation and interview techniques, including an analysis of several articles related to the implementation of the independent curriculum, the research found that a thorough understanding of curriculum concepts and structures is crucial. The primary concept in Pertiwi Gondangan Kindergarten's independent curriculum is the formation of a Pancasila student profile, featuring flexible learning and assessment processes. Assessment results are used by teachers to plan play activities and by parents to encourage children's play habits, reinforcing the role of parents as partners in the home. The structure of learning activities in the independent early childhood education curriculum comprises three integrated elements of learning outcomes within engaging activities. These outcomes in early childhood education include religious and moral values, character, identity, foundational literacy and numeracy, as well as science, technology, engineering, and art.